Asuhan Keperawatan Gerontik Pada Pasien Gout Arthritis Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Chyntia Viona Sari; Hasmita .; Sandra Dewi; Armaita . (CV. ITTC INDONESIA, 2026)
Based on data from the world health organization (WHO) in 2024, the prevalence of gout worldwide is 34,2%. In southeast asia, the prevalence of gout has reached 13 – 25% over the past 10 years. About 35% of gout ceses occur in men over 45 years old. The prevalence of gout among individuals aged 65 to 74 years is 51,9% and 54,8% the those aged 75 years. Gout arthritis is a condition in which there is excessive accumulation of uric acid in the body. Uric acid can potentially cause infection when tophi rupture, kidney failure, hypertension, and heart disease, leading to pain. If the pain is not treated promptly, it can result in disability in daily activity. The purpose of this study is to enable researchers to provide nursing care for elderly patients with gout. The research method used is a case study, in which the researcher selected one patient as a sample and applied nursing care. After assessment, the nursing diagnoses obtained were chronic pain, impaired physical mobility, and risk of falls. The interventions implemented included pain management, mobility support, fall prevention, and nursing implementation according to the planned care. After 5 days of implementation, the results showed reduced pain, decreased uric acid levels, and improved walking patterns. It is expected that patients will take medication regularly, routinely attend health check ups at the institution, and adopt a healthy lifestyle such as maintaining a proper diet, regular sleep, and adequate exercise according to their needs, as well as avoiding foods that mmay worsen their condition such as legumes, coconut milk, and green vegetables.